Cellular Regulation of the Uterine Microenvironment That Enables Embryo Implantation - Zenclussen, Ana Claudia; Hämmerling, Günter J. (Frontiers in Immunology, 2015)
Implantation of the fertilized egg into the maternal uterus is a crucial step in pregnancy establishment. Increasing evidence suggests that its success depends on various cell types of the innate immune system and on the fine balance between inflammatory and anti-inflammatory processes. In addition, it has recently been established that regulatory T cells play a superordinate role in dictating the quality of uterine environment required for successful pregnancy. Here, we discuss the cellular regulation of uterine receptivity with emphasis on the function and regulation of cells from the innate and adaptive immune system.